2018
DOI: 10.3390/pharmaceutics10030084
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Column-Switching HPLC-MS/MS Method and Clinical Application for Determination of Ethyl Glucuronide in Hair in Conjunction with AUDIT for Detecting High-Risk Alcohol Consumption

Abstract: It is critical to assess the severity of alcohol consumption in certain diseases such as alcohol liver disease and alcohol addiction. Ethyl glucuronide (EtG) is a highly stable metabolite of ethanol in hair; thus, it was proposed as a long-term monitoring marker for alcohol consumption. Therefore, an HPLC-MS/MS method for EtG in hair was developed and applied to a clinical setting to assess the relevance of the EtG concentration and/or the Alcohol Use Disorders Identification Test (AUDIT) score to high-risk al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…However, the reliability and validity of these instruments have not been fully established, and they are often used in conjunction with quantitative analysis of drugs and/or metabolites in peripheral biospecimens. Although combining drug use disorder screening test scores with analytical results has been shown to improve diagnostic performance in some cases [38,39], their efficacy has not been fully demonstrated, particularly in the diagnosis of MUD. Our previous studies have shown that there is no correlation between MA concentration in hair and drug use disorder screening test scores in current and former patients [28], indicating that hair analysis cannot monitor the recovery status of MUD patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reliability and validity of these instruments have not been fully established, and they are often used in conjunction with quantitative analysis of drugs and/or metabolites in peripheral biospecimens. Although combining drug use disorder screening test scores with analytical results has been shown to improve diagnostic performance in some cases [38,39], their efficacy has not been fully demonstrated, particularly in the diagnosis of MUD. Our previous studies have shown that there is no correlation between MA concentration in hair and drug use disorder screening test scores in current and former patients [28], indicating that hair analysis cannot monitor the recovery status of MUD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Segmental analysis of scalp hair provides information on the history of drug or toxicant exposure or toxicological changes over time [19,50,51]. The knowledge that scalp hair grows approximately 1 cm/month allows one to predict the period during which the drug was ingested, which has been often applied to test hair samples from drug-facilitated crimes [52,53,54,55] and post-mortem drug poisoning cases [36,38,56,57] for forensic purposes.…”
Section: Hair As a Metabolomics Samplementioning
confidence: 99%
“…For short-term occasional drinking or excessive drinking behavior, it can be detected by some alcohol metabolism-related indexes or organ damage-related indexes [2], such as blood-blood (and/or breath) ethanol content [3], acetaldehyde dehydrogenase (ALDH) [4], ethyl glucuronide (EtG) [5], ethyl sulfate (EtS), liver function indexes (GGT, ALT and AST) [6], fatty acid ethyl ester ( FAEE) [7], mean corpuscular volume (MCV) [8], and phosphatidylethanol (PEth).…”
Section: Introductionmentioning
confidence: 99%